Quantifying of morphological character for Kacang goat using principal component factor analysis - Lestari, D. A.; Sutopo, S.; Kurnianto, E.; Dagong, M. I. A.; Bugiwati, S. R. A.; Mamat-Hamidi, K.; Yakubu, A.; Pandupuspitasari, N. S.; Agusetyaningsih, I.; Kamila, F. T.; Setiaji, A. (Diponegoro University, 2024)
The study’s objective was to estimate the association among various linear body measurements and body weights of adult Kacang goats. The data was obtained from 209 heads of adult Kacang Goat, compressed 78 bucks and 131 ewes. The morphological evaluation was performed by measuring body weight (BW), body length (BL), chest depth (CD), chest girth (CG), chest width (CW), and withers height (WH). Factor PROCEDURE was performed to estimate the principal component. The result of factor analysis was used to determine the independent variable for linear regression analysis. BW has a favorable correlation with CG, BL, CD, CW, and WH for bucks and ewes. PC 1 accounts for 55.62% of the variation in bucks, while PC 2 accounts for an additional 18.34%. PC 1 accounts for just 0.45% of the overall variation in ewes, whereas PC 2 accounts for 0.24%. The R-squared (R2) values for bucks and ewes in the regression equation with CG as the independent variable are 0.32 and 0.41, respectively. For both bucks and ewes, the regression equation with CW as the independent variable had a higher R2 of 0.52 and 0.20, respectively. For bucks and ewes, the regression equation'sR2 values are 0.54 and 0.44, respectively, with combined CG and CW acting as independent variables. This integrated approach to analyzing body measurements in Kacang Goats provides a robust foundation for making informed decisions in goat farming.